The politics of Cannabis: Policies and their impact on youth: A case study in Phitsanulok province, Thailand - Pounpunwong, Wasan (Kasetsart Journal of Social Sciences, 2026)
This study utilizes qualitative research methods to examine the political aspects of cannabis legalization in Thailand, with an emphasis on its effects on youth in Phitsanulok Province after the drug policy changes implemented in 2021. The data collection process included a thorough examination of pertinent documents, literature, and interviews conducted with four primary groups: government officials, educators, youth representatives, and community members. Semi-structured interviews and content analysis were employed to collect and analyze findings. The research indicates that the cannabis legalization policy in Thailand was developed through political negotiations under the administration of Prime Minister Prayut Chan-o-cha. The recent policy change, especially the decision to remove cannabis from the controlled substances list, has initiated considerable social discourse. Cannabis presents acknowledged medical advantages; however, the current regulatory framework falls short in effectively overseeing its recreational use. The temporary guidelines issued by the Ministry of Public Health have been inadequate, leading to greater access and usage among young individuals, which negatively impacts their health, education, and family dynamics. Additionally, legal loopholes impede efficient state oversight. The study highlights the critical necessity for thorough legislation, particularly the swift enactment of the Cannabis and Hemp Act. Recommendations encompass enhanced packaging and advertising regulations, initiatives to raise public awareness regarding legal risks, and measures aimed at safeguarding youth. The implementation of these measures is essential for addressing social impacts, harmonizing cannabis regulation with national drug policies, and promoting a balanced approach to cannabis use in Thailand.